Incidence, presentation and outcome of acute aortic dissection: results from a population-based study - Johnny Steuer; Rebecka Hultgren; Christian Olsson; Christian Smedberg (Open Heart, 2024)
Objectives To describe the incidence of acute aortic dissection in a clearly defined population, to assess onset symptoms and admission biochemical marker levels and to analyse variables potentially associated to mortality.Methods Medical records and CT angiograms of all patients hospitalised for acute aortic dissection in the Stockholm County during the 5-year period 2012–2016 were reviewed. The patients were followed until date of death or until 31 December 2020. The annual incidence was determined. Associations between clinical and biochemical variables and 30-day mortality, respectively, were analysed using multivariable logistic regression models.Results A total of 344 patients were included. The mean annual incidence of acute aortic dissection was 4.1 per 100 000. Median age was 67 years (range 24–91) and 34% (n=118) were women. Type A dissection was predominant; 220 patients (64%) had type A and 124 (36%) had type B. Painless dissection was more common in type A than in type B (18% vs 15%, p=0.003). Type A dissection patients also more commonly had elevated plasma troponin T (44% vs 21%, p<0.001) and thrombocytopenia (26% vs 15%, p=0.010) than type B dissection patients on admission. Overall, 30-day mortality was 28% in type A and 11% in type B (p<0.001). Both painless dissection (OR 4.30, 95% CI 1.80 to 10.28, p=0.001) and elevated troponin T (OR 3.78, 95% CI 2.01 to 7.12, p<0.001), respectively, were associated with increased 30-day mortality in all acute aortic dissection patients. Thrombocytopenia was associated with elevated 30-day mortality only in patients with type A (OR 3.09, 95% CI 1.53 to 6.21, p=0.002).Conclusions Nearly two-thirds of acute aortic dissection patients had type A. Levels of troponin T and platelets, respectively, paired with presence or absence of typical symptoms may become useful adjuncts in risk stratification of patients with acute aortic dissection.